Twelve weeks supplementation with an extended-release caffeine and ATP-enhancing supplement may improve body composition without affecting hematology in resistance-trained men - Joy, J. M.; Vogel, R. M.; Moon, J. R.; Falcone, P. H.; Mosman, M. M.; Kim, M. P. (Journal of the International Society of Sports Nutrition, 2016)
Background: Increased ATP levels may enhance training-induced muscle accretion and fat loss, and caffeine is a known ergogenic aid. A novel supplement containing ancient peat and apple extracts has reported enhanced mitochondrial ATP production and it has been coupled with an extended-release caffeine. Therefore, the purpose of this investigation was to determine the effects of this supplement on body composition when used in conjunction with 12 weeks of resistance training.